Diatomaceous earth as an inorganic additive to reduce formaldehyde emissions from particleboards. Issue 2 (15th March 2017) - Funk, Monika; Wimmer, Rupert; Adamopoulos, Stergios
Abstract: The presented research is about the use of a new type of a functional inorganic additive in particleboards, for the purpose of reducing free formaldehyde releases. One-layered particleboards were prepared in the laboratory by mixing industrial wood particles and urea-formaldehyde resin. Natural, abundantly and cheaply available nano-mesoporous diatomaceous earth (DE) was used, without and in combination with urea as a scavenger. Silica quartz sand was also added as a nonporous analogy. Particleboards were pressed at two press factors (9 and 15 s/mm). Formaldehyde release was determined using the rapid 3-hour-flask method (DIN EN 717-3). As a result, DE additions insignificantly reduced bending properties of particleboards. Internal bonding was in part significantly lowered. The particleboard produced with 3% urea loaded on 5% DE prior to application almost halved (–45%) the formaldehyde release. Formaldehyde release was on the average 17% lower when pressed at 15 s/mm instead of 9 s/mm. By loading urea onto the nano-mesoporous structure of DE, an improved scavenging function of urea could be shown.